Effect of Angle of Attack on Drag and Lift Coefficients on Naca Airfoil for Wind Turbine Application - Adiwibowo, Priyo Heru; Purwanto, Aris; Rasyid, Akhmad Hafizh Ainur; Saepuddin, Ahmad (Graduate School of Universitas Syiah Kuala, 2025)
The development of renewable energy is expected not only to reduce dependence on fossil fuels but also to support the transition toward cleaner and more sustainable energy systems in the future. The combustion of fossil fuels significantly contributes to greenhouse gas emissions, thereby accelerating global climate change. Recognizing these limitations and negative environmental impacts, researchers and energy experts have begun to explore and develop various alternative energy sources that are more environmentally friendly and sustainable. Among them, wind energy is one of the most promising and widely available clean energy resources. The efficiency of wind turbines can be enhanced by optimizing the aerodynamic characteristics of their blades. This study examines the aerodynamic properties of three distinct NACA airfoil profiles: NACA 0012, NACA 2412, and NACA 3412. These profiles differ in camber magnitude and distribution, yet they share a maximum thickness of 12% of the chord length. Computational Fluid Dynamics (CFD) simulations were conducted using ANSYS Fluent with angles of attack ranging from -20 to 20. The results reveal that the NACA 2412 airfoil demonstrates the best aerodynamic performance at an angle of attack of 5, achieving the highest lift-to-drag ratio (L/D).